Direct effects of elevated dissolved CO2 can alter the life history of freshwater zooplankton - Lana Ramaekers; Tom Pinceel; Luc Brendonck; Bram Vanschoenwinkel (Scientific Reports, 2022)
Abstract Dissolved CO2 levels (pCO2) are increasing in lentic freshwaters across the globe. Recent studies have shown that this will impact the nutritional quality of phytoplankton as primary producers. However, the extent to which freshwater zooplankton may also be directly affected remains unclear. We test this in three model species representative of the main functional groups of primary consumers in freshwaters; the water flea Daphnia magna, the seed shrimp Heterocypris incongruens and the rotifer Brachionus calyciflorus. We experimentally exposed individuals to three pCO2 levels (1,500; 25,500 and 83,000 ppm) to monitor changes in life history in response to current, elevated and extreme future pCO2 conditions in ponds and shallow lakes. All species had reduced survival under the extreme pCO2 treatment, but the water flea was most sensitive. Body size and reproduction were reduced at 25,500 ppm in the water flea and the seed shrimp and population growth was delayed in the rotifer. Overall, our results show that direct effects of pCO2 could impact the population dynamics of freshwater zooplankton. By differentially modulating the life history of functional groups of primary consumers, elevated pCO2 has the potential to change the evolutionary trajectories of populations as well as the ecological functioning of freshwater communities.